Pengaruh Manajemen Modal Kerja Dan Rasio Keuangan Terhadap Profitabilitas Pada Industri Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (Bei) Pada Tahun 2017-2019 - Wahdah Lutfiana Arinta; Ronny Malavia Mardani; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis research was conducted with the aim. 1) To determine and analyze the effect of working capital management on profitability. 2) To determine and analyze the effect of liquidity on profitability. 3) To determine and analyze the effect of solvency on profitability. 4) To determine and analyze the effect of activities on profitability. The sampling method used was purposive sampling. The criteria that have been determined in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period, manufacturing companies that have positive working capital management during 2017-2019, manufacturing companies that issue financial reports using rupiah. and audited and reported reports at the end of December. Based on observations of these criteria, 36 companies were obtained. Methods of data analysis using quantitative methods using descriptive statistical testing, classical assumption testing, multiple linear analysis testing, t test (partial testing). The results showed that all working capital turnover (WCT) variables had a negative and significant effect on earnings per share (EPS), current ratio (CR). has no significant effect on earnings per share (EPS), the debt to equity ratio (DER) has a positive and significant effect on earnings per share (EPS), and total assets turnover (TAT) has no significant effect on earnings per share (EPS). Keywords: Working Capital Management, Financial Ratios, Current Ratio (CR), Debt To Equity Ratio (DER), Total Assets Turnover (TAT)